68.1k views
4 votes
NEED ASAP!!!!!

Solve the system by substitution.

{ 2.5x − 3y = −13
{ 3.25x − y = -14

User Lmeurs
by
5.2k points

2 Answers

3 votes

Explanation:

X


x = (- 13 + 3y)/(2.5)

Substitute that into the x of the other equation and solve for y

Lemme know if you need another step

User DoubleVoid
by
5.7k points
0 votes
Subtract 2.5x and move it to the other side to make it look like this : -3y =-2.5x -13. Then divide all by -3y and you get your answer
User Barry Carlyon
by
5.6k points